An Innovation Scheduling Program of Nurses During Covid-19 Pandemic: A Case Study - Kartika Mawar Sari; Rr. Tutik Sri Hariyati2; Titiek Muhaeriwati (International Journal of Nursing and Health Services (IJNHS), 2021)
The increasing number of COVID-19 patients in hospitals has impacted workload and nurse fatigue. Management of service schedules is necessary to protect the safety of patients and nurses. This case study aims to describe innovative programs in scheduling nurses during the COVID-19 pandemic. This study used the case study method, implementation analysis, and discussion with the literature. Data collection was conducted with interviews and secondary data. The samples were three heads nurse from three inpatient rooms. The process started from problem identification, problem analysis, planning of action, implementation, and evaluation. The results showed that the innovation program for scheduling during the COVID-19 pandemic could be implemented. The implementation was to prepare official schedule guidelines, simulation of the creation of official schedules, and socialization of draft guidelines for the office schedule to the Head nurse. Planning the official program during the COVID-19 pandemic required good management. Nursing managers could create schedules with excel-based formats that were easy to apply. Online socialization could be done to improve understanding. The use of information technology was necessary to create an easy, fast and workable scheduling formula. The nursing field can make policies related to scheduling during the COVID-19 pandemic, carry out implementation trials in units, monitoring and evaluating the implementation of innovative programs, and provide adequate internet connections.